The effect of hydrogen fuel on the performance and emissions of 3 kWe natural gas fuelled microturbine - Jomekian, Abolfazl; Alhasnawi, Bilal Naji; Bazooyar, Bahamin; Nabavi, Seyed Ali; Varasteh, Hirbod (Elsevier, 2024)
Hydrogen is an alternative fuel to power microturbines. In this work, the application of H2 in a 3 kWe microturbine combustor is investigated. First, the combustor is tested with different molar concentrations of hydrogen in methane fuel (XH2= 5%, 10% and 20%). Afterward, the operation of the microturbine is verified using thermodynamic analysis of the microturbine cycle. The combustion of the fuels is investigated using CFD analysis. The level of gaseous emissions including (CO2, CO, and NOX) and the microturbine overall operability in terms of turbomachine mechanical and thermal efficiencies are compared in each case to find out the influence of hydrogen addition on the natural gas combustion in the microturbine (MT). Findings show that the application of hydrogen in the MT combustor decreases the level of CO2 and CO emissions while increasing NOX emissions. Despite the improvement in combustion, hydrogen could deteriorate the MT effectiveness and overall efficiency. The findings demonstrate that if the hydrogen mole percent in the fuel rises from 0 to 10, the cycle efficiency decreases from 4.73% to 4.7% and if it increases to 20 percent, the efficiency of the cycle increases from 4.7% to 4.92%.
Keywords: 40 Engineering; 4017 Mechanical Engineering; 4002 Automotive Engineering; 7 Affordable and Clean Energy; Energy; 4004 Chemical engineering; 4012 Fluid mechanics and thermal engineering; 4019 Resources engineering and extractive metallurgy; Microturbine; Combustor; Hydrogen; Methane